Realizing synergy between the ministry of communication and informatics and the national cyber and crypto agency in the era of government digitalization - Usman, Reynaldi (Institute Of computer Science (IOCS), 2025)
In particular, overseeing cybersecurity and the protection of personal data in Indonesia has become more difficult in the modern digital age. Inconsistencies in policy often lead to disputes of authority between the National Cyber and Crypto Agency (BSSN) and the Ministry of Communication and Informatics (Kominfo), despite their strategic responsibilities in fostering digital transformation. The absence of effective governance is caused by the overlapping jurisdiction in managing personal data and cybersecurity, which is the fundamental concern. The purpose of this normative descriptive research is to examine legislative measures that might resolve the authority issue between the National Cyber and Crypto Agency and the Ministry of Communication and Informatics. This approach of study delves into both primary and secondary sources of law, including statutes, regulations, and case law from throughout the world. In order to construct a thorough analytical framework, the research also investigates public administration and state administration theories. Findings suggest that formal technical laws, improved coordination mechanisms, and alternative conflict resolution processes like mediation or arbitration may bring about authority synchronization. Furthermore, the efficacy of inter-agency cooperation may be enhanced by enhancing institutional capacity and incorporating best practices from other nations, including Singapore and the European Union. State sovereignty in the cyber world is intended to be strengthened by the proposals that follow, which should help establish a government that is more inclusive, responsive, and flexible in the face of digitalization's problems.